Beneficial effect of feeding a ketogenic diet to mothers on brain development in their progeny with a murine model of pyruvate dehydrogenase complex deficiency - Pliss, Lioudmila (Mol Genet Metab Rep, 2016)
Pyruvate dehydrogenase complex (PDC) deficiency is a major inborn error of oxidative metabolism of pyruvate in the mitochondria causing congenital lactic acidosis and primarily structural and functional abnormalities of the central nervous system. To provide an alternate source of acetyl-CoA derived from ketone bodies to the developing brain, a formula high in fat content is widely employed as a treatment. In the present study we investigated efficacy of a high-fat diet given to mothers during pregnancy and lactation on lessening of the impact of PDC deficiency on brain development in PDC-deficient female progeny. METHODS: A murine model of systemic PDC deficiency by interrupting the X-linked Pdha1 gene was employed in this study. RESULTS: Maternal consumption of a high-fat diet during pregnancy and lactation had no effect on number of live-birth, body growth, tissue PDC activity levels, as well as the in vitro rates of glucose oxidation and fatty acid biosynthesis by the developing brain of PDC-deficient female offspring during the postnatal age 35 days, as compared to the PDC-deficient progeny born to dams on a chow diet. Interestingly, brain weight was normalized in PDC-deficient progeny of high fat-fed mothers with improvement in impairment in brain structure deficit whereas brain weight was significantly decreased and was associated with greater cerebral structural defects in progeny of chow-fed mothers as compared to control progeny of mothers fed either a chow or high fat diet. CONCLUSION: The findings provide for the first time experimental support for beneficial effects of a ketogenic diet during the prenatal and early postnatal periods on the brain development of PDC-deficient mammalian progeny.